2022
DOI: 10.15294/jda.v14i1.33532
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Profitability on Indonesian’s Small Commercial Banking

Abstract: Purpose: The objective of this study is to decide whether the profitability of small banks is shaped by bank-specific and macro economic factors including liquid ratio, loan to deposits ratio, deposit to assets ratio, capital adequacy ratio, firm size, GDP growth, and inflation.Method: The sample selected using purposive sampling technique as many as 77 units of analysis consisting of 42 banks in the BUKU 1 category and 35 banks in the BUKU 2 category registered with OJK since 2014-2019. After eliminated the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similarly, Al Zaidanin and Al Zaidanin (2021) analyzed that the liquidity ratio have a very weak positive relationship on the return on assets. Likewise, Soesetio et al (2022) showed that liquidity positively affects small banks profitability in Indonesia. Moreover, Almaqtari et al (2019) found that liquidity ratio are found to have a significant positive impact on ROE.…”
Section: Liquidity Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Al Zaidanin and Al Zaidanin (2021) analyzed that the liquidity ratio have a very weak positive relationship on the return on assets. Likewise, Soesetio et al (2022) showed that liquidity positively affects small banks profitability in Indonesia. Moreover, Almaqtari et al (2019) found that liquidity ratio are found to have a significant positive impact on ROE.…”
Section: Liquidity Ratiomentioning
confidence: 99%
“…The results showed that working capital turnover has no effect on profitability, liquidity has no effect on profitability and leverage has a negative effect on profitability. Soesetio et al (2022) asserted whether the profitability of small banks is shaped by bankspecific and macro-economic factors. The results found that liquidity and loan to deposit ratio positively affects small banks profitability in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…A good LDR figure is in the range of 80% and 100% (Hasna et al, 2020). The LDR of a bank determines its profitability: the more credit given to customers, the less money is left idle, and the amount of interest revenue received rises (Soesetio et al, 2022). As a result, the LDR will increase, resulting increase in bank profitability.…”
Section: Loan To Deposit Ratio On Return On Assets (Roa)mentioning
confidence: 99%